2013
DOI: 10.1007/s13762-013-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Lead and nickel biosorption with a fungal biomass isolated from metal mine drainage: Box–Behnken experimental design

Abstract: The Pb(II) and Ni(II) biosorption of a fungal biomass isolated from mine drainage of metal-processing industries in Balya (Balıkesir province, Turkey) was optimized using a response surface methodology by altering parameters such as pH, initial metal concentration, contact time and biosorbent dosage. This strain was shown to be highly similar to Penicillium sp. Furthermore, zeta potential measurements and Fourier transform infrared spectroscopy were performed to understand the adsorption mechanism. A Box-Behnk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…These cell walls act as the first barrier to the incoming HM, serving to reduce its concentration (Hafez et al, 1997). Support of these results can be found in several studies where Pb(II) biosorption has been described as a major component of increased fungal tolerance mechanisms in P. chrysogenum, P. citrinum (Oso et al, 2015), P. janthinellum (Aytar, 2014;Iskandar et al, 2011), P. oxalicum (Svecova et al, 2006), P. purpurogenum (Say et al, 2003a) and P. smplicissimum (Iskandar et al, 2011). Specifically, dried P. simplcissimum has been tested as a biosorbent and has shown to adsorb 76.9 mg/g of Pb(II), with higher sorption rates at higher initial metal inoculation concentrations (Fan et al, 2008).…”
Section: Fungal Tolerance On Solid Mediamentioning
confidence: 59%
“…These cell walls act as the first barrier to the incoming HM, serving to reduce its concentration (Hafez et al, 1997). Support of these results can be found in several studies where Pb(II) biosorption has been described as a major component of increased fungal tolerance mechanisms in P. chrysogenum, P. citrinum (Oso et al, 2015), P. janthinellum (Aytar, 2014;Iskandar et al, 2011), P. oxalicum (Svecova et al, 2006), P. purpurogenum (Say et al, 2003a) and P. smplicissimum (Iskandar et al, 2011). Specifically, dried P. simplcissimum has been tested as a biosorbent and has shown to adsorb 76.9 mg/g of Pb(II), with higher sorption rates at higher initial metal inoculation concentrations (Fan et al, 2008).…”
Section: Fungal Tolerance On Solid Mediamentioning
confidence: 59%
“…The properties of certain types of microbial biomass make it possible to detoxify pollutants from industrial effluents and other aqueous solutions with low cost, easy availability and moderate operating conditions (Aksu, 2005;Dobson and Burgess, 2007;Fomina and Gadd, 2014). A variety of studies have focused on some microorganisms including bacteria (Aksu, 2005;Kwak et al, 2013), fungi (Mezaguer et al, 2013;Aytar et al, 2014) and yeast (Soares and Soares, 2012;Imandi et al, 2014), which are capable of absorbing pollutants from wastewater. However, the literature survey indicated that the studies relating to biosorption are very limited and only the purification of selected pollutants have been studied such as metals (Aytar et al, 2014;Hlihor et al, 2015) and dyes (Deniz and Ersanli, 2016;Deniz and Kepekci, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have focused on some microorganisms including bacteria (Aksu, 2005;Kwak et al, 2013), fungi (Mezaguer et al, 2013;Aytar et al, 2014) and yeast (Soares and Soares, 2012;Imandi et al, 2014), which are capable of absorbing pollutants from wastewater. However, the literature survey indicated that the studies relating to biosorption are very limited and only the purification of selected pollutants have been studied such as metals (Aytar et al, 2014;Hlihor et al, 2015) and dyes (Deniz and Ersanli, 2016;Deniz and Kepekci, 2016). There is a need to study other pollutants, especially PFOA which are not easily biodegradable, and to identify the specific species which can provide abundant biomass with simple growth conditions, inexpensive media and high biosorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fungi are suitable bioremediation agents with favorable prospects for the enrichment of radionuclides from liquid wastes [19]. Generally, the surface of fungal mycelia is negatively charged in ambient pH [22], and the cationic radionuclides can be adsorbed on these fungi easily [23][24][25].…”
Section: Introductionmentioning
confidence: 99%